Challenges, opportunities and progress in solid waste management during COVID-19 pandemic. (September 2020) - Tripathi, Abhilasha; Tyagi, Vinay Kumar; Vivekanand, Vivekanand; Bose, Purnendu; Suthar, Surindra
Abstract: At the end of December 2019, Wuhan City became the epicenter of the highly contagious virus known as the novel coronavirus. Now that mid-2020 has already passed, almost every country is adversely affected by Corona Virus Disease (COVID-19). The routine activities of people of all ages are overturned, which has led to a shift in the trends of waste created by households, streets, and most importantly, medical facilities and quarantine centers. Compulsive use of personal protection equipment such as masks, gloves, sanitizers, etcetera by the frontline workers from the medical sector, banks, daily need stores, waste collection industries, etc. and the use of masks by every common man stepping out has skewed the trend of waste generation to a different direction. Recently, the replacement of single-use plastic was accepted by the masses, and the pandemic suddenly rebounded to the previous situation, it is expected to be worse in the long run. Another secondary outcome is reduced waste collection and recycling due to lockdown, leading to a pile-up of wastes. But several nations are adopting strategies to break the transmission chain of the virus by trying to minimize human contact. The study discusses the effect of COVID-19 on the generation, recycling, and disposal of solid waste. A brief collection of different countries' efforts to restrict the transmission of virus through solid waste is also discussed. Graphical abstract: Image 1 Highlights: The use of single-use plastic is expected to increase to alarming levels during the pandemic. Waste recycling is adversely affected lately but can be administered by suitable management practices. Sufficient resting time (up to 72 ​h) should be provided to properly sealed waste. Resting time augment the virus elimination and break the transmission chain.